Comparative Study: The Impact Of Domestic Structure And Trade Cooperation On Exports Of Developed And Developing Countries In Asia - Ilmiawan, Muhammad Iqbal; Asmara, Kiky; Nisa, Fauzatul Laily (RISK : Jurnal Riset Bisnis dan Ekonomi, 2025)
The intensification of globalization has driven greater economic integration through various international trade agreements such as FTA, CEPA, and RTA, particularly in Asia, which is the region with the highest number of trade agreements in the world. However, the benefits of such integration have not been evenly distributed between developed and developing countries. This study aims to comparatively analyze the impact of domestic structures reflected through labor, capital, HDI, exchange rate, and trade cooperation on exports in developed and developing countries in Asia. This research employs a quantitative approach using panel data from 17 countries (5 developed and 12 developing) over the 2004–2023 period, analyzed using the Error Correction Model (ECM). The results reveal that, in the long run, all variables significantly affect exports in developing countries except for trade cooperation, which shows no significant impact. In developed countries, only labor has no significant effect on exports, while other variables exhibit significant influences. These findings indicate that developed countries tend to be capital-intensive, whereas developing countries are more labor-intensive. In the short run, only labor and HDI significantly affect exports in developing countries, while in developed countries, capital and exchange rate have significant effects on exports. Furthermore, the existence of cointegration suggests an adjustment process from the short run to the long run, with the speed of adjustment in developing countries being relatively slower than in developed ones.